Design, Synthesis, and Evaluation of Neomycin‐Imidazole Conjugates for RNA Cleavage. Issue 11 (23rd September 2022) - Martin, Céline; Bonnet, Maurinne; Patino, Nadia; Azoulay, Stéphane; Di Giorgio, Audrey; Duca, Maria
Abstract: Targeting RNA with synthetic small molecules attracted much interest during recent years as a particularly promising therapeutic approach in a large number of pathologies spanning from genetic disorders, cancers as well as bacterial and viral infections. In this work, we took advantage of a known RNA binder, neomycin, to prepare neomycin‐imidazole conjugates mimicking the active site of ribonuclease enzymes able to induce a site‐specific cleavage of HIV‐1 TAR RNA in physiological conditions. These new conjugates were prepared using a straightforward synthetic methodology and were studied for their ability to bind the target, inhibit Tat/TAR interaction and induce selective cleavage using fluorescence‐based assays and molecular docking. We found compounds with nanomolar affinity, promising cleavage activity and the ability to inhibit Tat/TAR interaction with submicromolar IC50 s. Abstract : New RNA binders : a straightforward synthetic methodology allowed to obtain new neomycin conjugates containing an imidazole residue mimicking the active site of ribonuclease enzymes able to induce a site‐specific cleavage of HIV‐1 TAR RNA in physiological conditions. We found compounds with excellent affinity, promising cleavage activity and the ability to inhibit Tat/TAR interaction with submicromolar IC50 s.